DEVELOPMENT AND VALIDATION OF NOVEL RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF SALICYLIC ACID AND BECLOMETHASONE DIPROPIONATE IN A TOPICAL OINTMENT DOSAGE FORM - Sawant, Vanita; Mali, Chinmayi; jain, vandana (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to develop and validate an analytical method to simultaneously estimate salicylic acid (SA) and beclomethasone dipropionate (BD) in a topical ointment formulation. Methods: The simultaneous estimation of SA and BD in a topical ointment formulation was carried out by developing and validating a novel, accurate, and economical isocratic reversed-phase high-performance liquid chromatographic (RP-HPLC) method. Separation was achieved by chromatographic technique using a prontosil HPLC C18 (250×4.6 mm) column with a particle size of 5 μm. The mobile phase utilized for this study includes methanol, acetonitrile, and 0.1% orthophosphoric acid in the ratio 50:35:15 v/v/v, respectively. The flow rate of 1 mL/min and column temperature of 28±2°C were set. The detection of the two drugs was carried out at 235 nm using an ultraviolet detector. It was observed that SA and BD were retained at 3.59 min and 6.00 min, respectively. Results: The RP-HPLC method was found to be linear with excellent correlation between peak areas and concentrations of 30–108 µg/mL for SA and 1–3.6 µg/mL for BD. The observed recovery data was obtained within the acceptance range of 98–102%, which confirmed the accuracy of the developed method. The two drugs, SA and BD, showed good resolution with a short analysis time of 7 min. Conclusion: The method was successfully created and validated in compliance with the recommendations of the International Conference on Harmonization for specificity, precision, linearity, accuracy, and robustness.